Analysis of Challenge and Barrier Factors in Implementing ESG Concept in Indonesia’s Construction Sector - Wira Andini; Farida Rachmawati (SENTRI: Jurnal Riset Ilmiah, 2026)
The growing urgency of sustainability issues, including environmental degradation, social inequality, and governance weaknesses, has intensified global pressure on industries to adopt Environmental, Social, and Governance (ESG) principles. The construction sector, as one of Indonesia’s major economic contributors and a significant source of global carbon emissions, faces increasing demand to align its practices with sustainability goals. Despite this urgency, ESG implementation in the Indonesian construction industry remains limited due to low awareness, inconsistent frameworks, and regulatory challenges. This study aims to identify key challenges and barriers to ESG implementation within Indonesia’s construction sector and to formulate strategic recommendations for improvement. A descriptive quantitative method was applied using a survey distributed to construction experts and practitioners across Jakarta, Surabaya, and Bandung. Data were analyzed using the Relative Importance Index (RII) to determine the relative weight of each factor influencing ESG implementation. The results indicate that the main challenges include a lack of ESG socialization and education, short-term profit orientation, and limited stakeholder engagement, with RII values ranging from 0.44 to 1.00. Meanwhile, the main barriers are limited financial capacity, the absence of standardized reporting frameworks, and weak regulatory support, with RII values between 0.60 and 0.96. These findings suggest that ESG implementation in Indonesia’s construction sector remains in its early stages, hindered by institutional and governance constraints. Strengthening ESG literacy, policy frameworks, and financial mechanisms is essential to accelerate sustainable construction practices and support national development goals.